3D Cellulose Graphene Aerogel with Self‐Redox CeO2 as Li2S Host for High‐Performance Li–S Battery. Issue 12 (22nd September 2022) - Yu, Hao; Zhou, Xi; Zeng, Peng; Guo, Changmeng; Liu, Hong; Guo, Xiaowei; Chang, Baobao; Chen, Manfang; Su, Jincang; Wang, Xianyou
Abstract : Lithium sulfide is considered the promising cathode material of a Li–S battery because of its high theoretical capacity, high melting point, affordable volume expansion, and lithium composition. However, the quick capacity fading and high activation energy barrier due to low electronic and ionic conductivity and polysulfide shuttle effect still restrict the practical application of the Li2 S cathode. Herein, CeO2 is introduced with unique self‐redox characteristics into cellulose graphene aerogel (CGA) with the 3D interconnected structure (CGA/CeO2 ) as the host of Li2 S. It is found that CGA/CeO2 can provide plentiful three‐phase boundary for the chemisorption to LiPSs through the strong polarity of CeO2 . Moreover, the ultrastrong polarity of CeO2 can restrain the LiPSs shuttle, and CeO2 can spontaneously oxidize polysulfide, thus boosting the conversion reaction kinetics and comprehensive electrochemical performances of Li–S battery based on Li2 S cathode. As a result, these features reciprocate Li2 S‐CGA/CeO2 cathode excellent electrochemical performances. Therefore, this work not only provides a significant exploration for the mechanical explanation of the cerium oxide catalytic conversion reaction but also provides a brand‐new idea for the excellent electric catalyst for the catalytic conversion reaction of polysulfide in lithium–sulfide batteries. Abstract : Cellulose graphene aerogel (CGA) reveals a 3D interconnected structure. The introduced CeO2 crystal possesses the self‐redox property that can partly convert the valence state of the Ce element. Ce 4+ can promote the reaction kinetics of the Li–S battery by oxidizing LiPSs to thiosulfate. The prepared Li2 S‐CGA/CeO2 cathode exhibits excellent electrochemical properties.